Idea to script storytelling for today's media - Hyde, Stuart Wallace 1923- (Allyn and Bacon, 2003)
Idea to Script: Storytelling for the Electronic Media explores how to conceive and write compelling stories for the electronic media. Idea to Script has a unique two-part structure: Part One lays the foundation for conceptualizing and writing effective scripts and Part Two focuses on the development of scripts from conception to execution. It examines the nature of comedy, melodrama and tragedy; it presents ways of structuring the incidents within stories to achieve maximum effectiveness; it introduces and illustrates the nature and importance of catharsis in the storytelling arts; it presents a vast number of universal themes that have marked the most successful stories of all time; and it asks students to direct their stories to the needs, desires, fears and hopes of their audiences. For anyone interested in launching a successful career in the media.